The oldest psyllipsocid booklice, in Lower Cretaceous amber from Lebanon (Psocodea, Trogiomorpha, Psocathropetae, Psyllipsocidae) - Dany Azar; André Nel (ZooKeys, 2011)
Libanopsyllipsocus alexanderasnitsyni gen. et sp. n., of Psyllipsocidae is described and figured from the Lower Cretaceous amber of Lebanon. The position of the new taxon is discussed and the fossil is compared to other psyllipsocids. The species represents the earliest record of the family Psyllipsocidae.